(untitled) (Research, Society and Development, 2020)
This study aimed to analyze the conception of students from a rural school in relation to technologies, as well as to verify issues related to access and its use. It is a qualitative and case study, developed with 54 students of 6th, 7th, 8th and 9th years of a public school, located in the municipality of Santa Maria in Rio Grande do Sul. A questionnaire was applied with open and closed questions, in which it was found that most students use television and cell phones in their daily lives. To this end, the importance of these being understood as more than mere tools to support pedagogical practice or simple tools to make the class more interesting is highlighted. The use of TDIC in schools needs to have a critical appropriation in what involves students and teachers before the construction of knowledge, these need to be built collectively.